The Trend of Metacognition Research Trend in Learning Biology in Indonesia - Idris, Tengku; Rahmat, Adi; Hidayat, Topik (KnE Social Sciences, 2024)
This literature review aimed to get an overview of metacognition research in learning biology in Indonesia. Data were taken from Biology Education journals that had been accredited by the Ministry of Education and Culture in 2023. 20 journals, consisting of Sinta 2 and Sinta 3, journals were analyzed. Within the journals, 43 research articles were analyzed. Some of the aspects analyzed were the type of research, research subjects, instruments used, data analysis methods, treatments used and themes or topics. Data analysis showed that the majority of research conducted was experimental research, followed by Korean research. The most researched subjects were high school students, followed by college and junior high school students. In metacognition research in Indonesia, researchers often used the MAI instrument, and it is not completely defined. T-test analysis was the most used means of processing data, followed by descriptive data processing in the form of percentages. The topics used in the research showed that all topics were suitable for training students’ metacognition. Keywords: metacognition, research trend, MAI instrument